Alerta temprana de incendios para la temporada 2025-2026 para el noreste rionegrino - Devesa, Antonia; Neira Zilli, Fernanda; Echevarria, Daniela Carola; Villablanca, Mariana; Marinzalta, Mauro Andres; Segura, Atilio Ramon; Millapi, Leandro; Leoni, Germán; Serra, Raul; Cariac, German; Giovine, Pablo Martin; Van Konijnemburg, Juliana; et al. (EEA Valle Inferior, INTA, 2025)
EEA Valle Inferior